2022
DOI: 10.3389/fcimb.2022.886196
|View full text |Cite
|
Sign up to set email alerts
|

The Difference of Gut Microbiota and Their Correlations With Urinary Organic Acids Between Autistic Children With and Without Atopic Dermatitis

Abstract: Autism is a kind of biologically based neurodevelopmental condition, and the coexistence of atopic dermatitis (AD) is not uncommon. Given that the gut microbiota plays an important role in the development of both diseases, we aimed to explore the differences of gut microbiota and their correlations with urinary organic acids between autistic children with and without AD. We enrolled 61 autistic children including 36 with AD and 25 without AD. The gut microbiota was sequenced by metagenomic shotgun sequencing, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 103 publications
0
3
0
Order By: Relevance
“…Furthermore, another study in a Chinese cohort found similar results to ours; F. plautii increased as the CKD severity increased [ 6 , 12 , 21 ]. Finally, enriched A. caccae levels have been observed in chronic inflammatory atopic dermatitis [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, another study in a Chinese cohort found similar results to ours; F. plautii increased as the CKD severity increased [ 6 , 12 , 21 ]. Finally, enriched A. caccae levels have been observed in chronic inflammatory atopic dermatitis [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous subtyping strategies are mostly defined by some particular symptom characteristics, such as social behavior or language ability ( 6 , 7 , 9 , 10 ). Another feasible approach is using biomedical features to stratify samples to reduce heterogeneity and produce subgroups which are more likely to share a more similar phenotype and etiology ( 11 , 12 , 59 ). Compared to the behavioral symptom characteristics, using biomedical features as subtyping indicators has some advantages, because they are more objective and easily to measure, more directly to indicate the possible mechanisms underlying the associated heterogeneity, and could also provide useful information to further explore the potential targets to facilitate the development of individualized biomedical therapy strategies for certain ASD subtypes.…”
Section: Discussionmentioning
confidence: 99%
“…The alpha diversity of the gut microflora was lower in the AD group. AD patients showed a higher abundance of Anaerostipes caccae, Eubacterium Hallii, and Bifidobacterium bifidum compared to controls, while the control group had a higher abundance of Akkermansia muciniphila, Roseburia intestinalis, Haemophilus parainfluenzae, and Rothia mucilaginosa [74].…”
Section: Atopic Dermatitismentioning
confidence: 91%